STRATEGI BERTAHAN HIDUP BURUH TANI DI KECAMATAN DANAU KEMBAR ALAHAN PANJANG - Yuni Aster Juanda; Bob Alfiandi; Indraddin Indraddin (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Farmers in Alahan Panjang, Danau Kembar Subdistrict, are generally in the poverty line. Various efforts made by farm workers to survive and improve their standard of living. The purpose of this research is to describe the strategy of surviving farm laborers in the Alahan Panjang Twin Lake District. The results of the study show that the survival strategies carried out by farm workers have three strategies, namely active strategy, passive strategy and network strategy. An active strategy where farm workers use ways to exploit potential and talent, increase employment and income, increase working hours and buy and sell businesses online as a way of survival. Passive strategy, where farm workers use ways to save expenses and minimize needs as a way of survival. Network strategy, where farm workers use ways to utilize relationships and acquaintances and owe it to neighbors and relatives as a way of survival.